Penilaian Kinerja Guru Produktif Dalam Melaksanakan Standar Kompetensi Guru - Dedi Setiawan; Hendra Dani Saputra; Muslim Muslim; R Chandra (Universitas Negeri Padang, 2020)
Abstract— This study aims to assess teachers in education. This type of research is combination research (quantitative and qualitative). Research subjects were 55 people. The research data was obtained through questionnaires, peers, interviews, and data from the analysis using a percentage formula. The results of the study found that pedagogic competence: (1) For the questionnaire the average total score was 4.2. (2) For peer rankings average total score of 4.0, with the achievement level of respondents 80% remaining in the